2016
DOI: 10.1016/j.palaeo.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and chemostratigraphy of a Toarcian black shale hosting Mn-carbonate microbialites (Úrkút, Hungary)

Abstract: is really a grey shale with moderate to low TOC content that accumulated in a starved basin. The 33 organic matter content and anoxic characteristics resulted from rapid accumulation of microbial 34 organic matter from microbial booms, accompanied by a geothermally generated hydrothermal 35 circulation system, and a high rate of authigenic mineral formation (clay minerals and proto-ore 36 minerals). The inferred enzymatic Mn and Fe oxidation blocked carbonate formation by 37 decreasing the pH. The system remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The mineralogical composition of the Mn ore is dominated by Mn-carbonate (Ca-rhodochrosite and kutnohorite) along with Fe minerals (goethite, pyrite, celadonite, and Fe-smectite). Mn ore beds are separated by the black shale host (Polgári et al, 2013(Polgári et al, , 2016a. The entire ore bed is composed of millimeter-scale woven structures with widespread microbe fossils, indicating a biogenetic origin for the Mn-carbonate deposit, and both Mn and Fe are initially enriched in the biomats (Polgári et al, 2007(Polgári et al, , 2012a(Polgári et al, ,b, 2013(Polgári et al, , 2016a).…”
Section: Comparison Of the Cryogenian Dfmnd In South China With The Jmentioning
confidence: 99%
See 1 more Smart Citation
“…The mineralogical composition of the Mn ore is dominated by Mn-carbonate (Ca-rhodochrosite and kutnohorite) along with Fe minerals (goethite, pyrite, celadonite, and Fe-smectite). Mn ore beds are separated by the black shale host (Polgári et al, 2013(Polgári et al, , 2016a. The entire ore bed is composed of millimeter-scale woven structures with widespread microbe fossils, indicating a biogenetic origin for the Mn-carbonate deposit, and both Mn and Fe are initially enriched in the biomats (Polgári et al, 2007(Polgári et al, , 2012a(Polgári et al, ,b, 2013(Polgári et al, , 2016a).…”
Section: Comparison Of the Cryogenian Dfmnd In South China With The Jmentioning
confidence: 99%
“…indeed, Mn enrichment itself serves as an indicator for obligatory oxic conditions in the geological record (Maynard, 2010;Johnson et al, 2016b). Changes in oxygen supply determined whether Mn ores (the enzymatic Mn oxidation engine starts under obligatory oxic conditions) or black shales (formed under slightly decreasing oxygen supply) accumulated in both the post-Sturtian Nanhua Basin (Zhang et al, 2015;Yu et al, 2016) and the Early Jurassic Úrkút Basin (Polgári et al, 2012a(Polgári et al, , 2016a. The oxic and low temperature (<100˚C) aquatic systems would have favored microbially mediated Mn(II) oxidation in both locations (Tebo et al, 2004;Tang et al, 2013).…”
Section: Comparison Of the Cryogenian Dfmnd In South China With The Jmentioning
confidence: 99%
“…The Chinese study shows more similarities to the manganese ore formation found in Hungary than the Brazilian study does. There are about 480 million years between the Úrkút and the Datangpo formations; however, the processes characterizing their ore enrichment and metallogenetic mechanisms are similar (Polgári et al, 2012a, b, 2013, 2016a,b; Molnár et al, 2017; Yu et al, 2019). Both of them are Mn carbonate (Ca rhodochrosite and kutnohorite) ore in black shale environment, in which only the amount of iron differs.…”
Section: Discussionmentioning
confidence: 99%
“…A discontinuous chert layer (Cservár Flintstone Member) represents the closes part of the formation (Bíró 2014). For further details on the geology and stratigraphy of the Úrkút Mn ore deposit, see Szabó and Grasselly (1980), Szabó et al (1981), Grasselly and Pantó (1988), Polgári et al (1991Polgári et al ( , 2012Polgári et al ( , 2013Polgári et al ( , 2016a, Pantó et al (1996), Haas (2012) and Bíró (2014).…”
Section: Geological Settingmentioning
confidence: 99%